Su un divergente accordo. Perlini, Cacciari e la critica del principio-speranza - Cerasi, Enrico (Filosofia, 2017)
This paper discusses Tito Perlini and Massimo Cacciari’s critiques of Bloch’s “Principle of Hopes”. Even though Perlini and Cacciari move from different starting points, they both assert that, unlike the gnostic myths, Bloch’s Utopia should result from an analysis of reality. Yet Perlini, following the Adornian Negative Dialektik, stresses the alienation of humankind in the capitalistic society, while Cacciari – his theoretical philosophy in particular – contends that the aim of philosophy (from Plato to Wittgenstein) is to show the transcendence of the thing intended as the human logos.